Molecular breast imaging and background uptake of fibroglandular tissue as tools to predict neoplasms in dense breasts - Viviani, Carla Lima Santos; Veras, Lucimara Priscila; Viviani, Dionísio Nepomuceno; Amorim, Rivadávio Fernandes Batista de (Mastology, 2021)
The sensitivity of mammography as a screening method is low in dense breasts, which are associated with a high risk of developing tumors. Thus, molecular breast imaging (MBI) with background uptake (BPU) of fibroglandular tissue can be used as a complementary method. The aim of this review was to synthesize the existing evidence on these important diagnostic imaging tools. Three electronic databases were searched to identify original articles, including publications dating from September 2010 and September 2020, in English, conducted in any location, and addressing at least one aspect related to dense breasts and Breast-specific gamma-imaging (BSGI). In total, 22 studies were reviewed. Several advantages of MBI and BPU as complementary methods of screening for dense breasts were found. Among them, we can mention the increase in breast cancer detection rate, easy implementation in clinical practice, high patient satisfaction, low cost and good reproducibility. In view of the good results found in our review, we can conclude that the implementation of MBI, especially with BPU, can be a promising complementary tool for screening of dense breasts.